PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH RUMAH TANGGA UNTUK MENGATASI PERMASALAHAN KONDISI TANAH DI DESA SELAT KABUPATEN LOMBOK BARAT - Al Farizi, Abdul Haris; Dewi, Gusti Ayu Gayatri Sinta; Rosy, Muhammad Fahrur; Humairo, Cinta Aisya; Makagiansar, Dyaz; Danisa, Farah Athiyah; Anggraeni, Baiq Susthia Sukma; Fatiyya, Raisa Gina; Melinda, Baiq Widya Putri; Rozina, Eka (Universitas Mataram, 2023)
The problem that often becomes a concern in Selat Village is the unhealthy condition of the paddy fields due to continuous application of chemical fertilizers and household waste that is not used properly. This is due to a lack of public understanding of the problems. Therefore, it is necessary to conduct counseling through training in the making of liquid organic fertilizer which aims to increase public understanding of how to make Liquid Organic Fertilizer from household waste as a way to overcome the problem of household waste and can be used to improve the condition of rice fields in Selat Village. The method used in this activity is socialization and training in making liquid organic fertilizer with local microorganisms from stale rice. The results obtained from this activity are that the community is able to understand how to manage household waste, especially stale rice into liquid organic fertilizer to overcome household waste problems and can cultivate paddy fields in Selat Village.